miRNAs involved in the regulation of exercise fatigue - Niu, Siyuan; Yin, Xiupeng; Cao, Qinglei; Huang, Kaiyu; Deng, Zhongyuan; Cao, Jie (Frontiers in Physiology, 2025)
Exercise-induced fatigue refers to a temporary decline in physiological function resulting from prolonged or high-intensity exercise, which is characterized by decreased muscle strength, diminished exercise performance, and heightened subjective feelings of fatigue. The study of exercise fatigue holds significant importance not only in competitive sports and public health, but also extends to medicine, military applications, and occupational safety. MicroRNA (miRNA) represents a class of non-coding RNA that plays a pivotal role in the regulation of gene expression. The involvement of miRNAs in exercise-induced fatigue has garnered increasing attention within the scientific community. This article provides an overview of fundamental concepts and biological functions associated with miRNAs, defines and classifies exercise fatigue while outlining its physiological changes, emphasizes alterations in miRNA expression during episodes of exercise-induced fatigue, and conducts an in-depth analysis regarding the mechanisms through which miRNAs influence this phenomenon via modulation of energy metabolism, inflammatory responses, and oxidative stress. Furthermore, this article anticipates future research directions as well as potential clinical applications for miRNAs concerning exercise-induced fatigue. This review holds significant importance for elucidating the molecular mechanisms underlying exercise-related fatigue while fostering advancements within sports medicine and rehabilitation science.